2018
DOI: 10.1152/ajpregu.00248.2018
|View full text |Cite
|
Sign up to set email alerts
|

Activation of µ-opioid receptors in the rostral ventrolateral medulla blocks the sympathetic counterregulatory response to glucoprivation

Abstract: Intensive insulin therapy is the gold standard for managing serum glucose levels in patients with insulin‐deficient diabetes mellitus. Hypoglycaemia‐associated autonomic failure (HAAF) is a clinical syndrome characterised by the absence of a glucose counter‐regulatory response to hypoglycaemia or glucoprivation. The precise physiologic mechanisms underlying HAAF remain unknown. Recent data from human studies suggests activation of the endogenous opioid system during antecedent hypoglycaemia may contribute to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Both C1 and non-C1 neurons in the ventrolateral medulla contain µ-opioid receptor-immunoreactive synaptic inputs that reduce neuronal efferent signaling upon activation (1, 2, 17, 18, 33, 36). Recently, we also showed that the selective activation of µ-opioid receptors in the rostral ventrolateral medulla attenuates adrenal sympathetic outflow by ~50% and completely blocks the counterregulatory response to glucoprivation (22). To the best of our knowledge, it remains unknown whether C3 neurons also contain µ-opioid receptor-immunoreactive synaptic inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Both C1 and non-C1 neurons in the ventrolateral medulla contain µ-opioid receptor-immunoreactive synaptic inputs that reduce neuronal efferent signaling upon activation (1, 2, 17, 18, 33, 36). Recently, we also showed that the selective activation of µ-opioid receptors in the rostral ventrolateral medulla attenuates adrenal sympathetic outflow by ~50% and completely blocks the counterregulatory response to glucoprivation (22). To the best of our knowledge, it remains unknown whether C3 neurons also contain µ-opioid receptor-immunoreactive synaptic inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Pentobarbital exerts its anesthetic effects by acting on inhibitory GABA receptors and hence can cause quite severe cardiorespiratory depression ( Field et al, 1993 ), an effect described in dogs over 40 years ago ( Cox and Bagshaw, 1979 ). Pentobarbital suppresses both sympathetic and parasympathetic arms of cardiovascular reflexes; however, is still used in studies investigating autonomic cardiovascular control ( Solomon et al, 1999 ; Nedoboy et al, 2016 ; Kakall et al, 2018a ) since these effects appear to be minimal if anesthetic depth is tightly controlled ( Eikermann et al, 2009 ). Unlike the other anesthetics mentioned, pentobarbital does not raise blood glucose levels ( Sano et al, 2016 ; Windelov et al, 2016 ) and is used in anesthetized studies investigating the glucoregulatory system ( Korim et al, 2016 ), so it was chosen for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the supraphysiological nature of the challenge is a notable feature of previously reported anesthetized experiments. To stimulate a measurable sympathoadrenal reflex, large doses of 2-DG are administered ( Kakall et al, 2018a ). To stimulate a similar level of catecholamine release in pentobarbital anesthetized dogs, compared with conscious dogs, a 3× greater dose of 2-DG was needed ( Taborsky et al, 1984 ), which was also the same dose used in anesthetized rats ( Kakall et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the aim of this study was to test the effects of dietary ketosis, induced by a 3 week KD, on components of the sympathoadrenal CRR to severe insulin-induced hypoglycemia in healthy, nondiabetic rats, by measuring adrenal sympathetic nerve activity (ASNA), adrenal gland activity, and epinephrine release, as well as the activation state of catecholaminergic C1 neurons in the brainstem, which are glucose-sensitive and involved in the hypoglycemic CRR [ 23 , 24 ]. The adrenal sympathetic nerve, unlike renal, lumbar, or muscle sympathetic nerves, is activated by hypoglycemia independent of elevated insulin levels [ 25 ] and can be acutely recorded in anesthetized rats [ 26 ]. As ASNA positively correlates with epinephrine release [ 27 ], and the actions of epinephrine on target tissues produces physical symptoms of hypoglycemia, in vivo ASNA recordings in anesthetized rats can provide a sensitive, real-time measure of hypoglycemia progression without confounders such as handling stress, multiple blood draws for plasma epinephrine quantification, and difficulties in registering mild physical symptoms in conscious animals.…”
Section: Introductionmentioning
confidence: 99%